High Electric Field Enhancement Induced by Modal Coupling for a Plasmonic Dimer Array on a Metallic Film - Jiawei Liu; Ziming Meng; Jinyun Zhou (Photonics, 2024)
A giant electric field on a subwavelength scale is highly beneficial for boosting the light–matter interaction. In this paper, we investigated a hybrid structure consisting of a hemispheric dimer array and a gold film and realized resonant mode coupling of the surface lattice resonance (SLR) and surface plasmon polariton (SPP). Mode coupling is demonstrated by observing anti-crossing in reflection spectra, which corresponds to Rabi splitting. Although the resonance coupling does not enter the strong coupling regime, an improved quality factor (Q~350) and stronger electric field enhancement in the gap region of the dimer (i.e., hot spot) in our hybrid structure are obtained compared to those of the single dimer or dimer array only. Remarkably, the magnitude of electric field enhancement over 500 can be accessible. Such high field enhancement makes our hybridized structure a versatile platform for the realization of ultra-sensitive biosensing, low-threshold nanolasing, low-power nonlinear optical devices, etc.